Seorang Wanita Usia 23 Tahun Dengan Anemia Mikrositik Hipokromik Suspect Systemic Lupus Erythematosus (SLE) - Sri Meutia; Regina Keumala Sabty (Jurnal Medika Nusantara, 2023)
Systemic Lupus Erythematosus (SLE) is an autoimmune inflammatory disease with diverse clinical manifestations, disease course and prognosis, and it is difficult to predict the onset of acute and subtle manifestations, can attack various organs of the body, and can recur. Hematological manifestations in SLE occur frequently and are one of the criteria for ACR. Thrombocytopenia occurs in 25% - 50% of patients, leukopenia occurs in around 50% and hemolytic anemia with positive Coombs test results in around 10%. Cytopenia that occurs is usually the result of peripheral damage mediated by autoantibodies that cause bone marrow hypercellularity. In rare cases, hypocellularity occurs in the bone marrow due to mediation of T cells that inhibit hemopoetic cells, which causes bone marrow failure and causes anemia gravis. A 23 year old woman came with complaints of paleness, fatigue, decreased appetite, joint pain, nausea, vomiting, headaches, dizzy eyes. On laboratory examination on June 12 2023, microcytic hypochromic anemia was found, on June 13 2023, microcytic hypochromic anemia was found, on peripheral blood morphology examination, anemia was suspected due to iron deficiency, and there was a bacterial and parasitic infection process, on June 15 2023, hypokalemia was found. , hyperchloremia, hypocalcemia. On June 16, 2023, microcytic hypochromic anemia was found. On ECG examination, benign Ves arrhythmia was found. On chest examination, the lung showed no abnormalities, the cast size was normal. On ultrasound examination, Nephrolithiasis Dextra was found. So it was found on physical examination, and the patient’s supporting examination was confirmed as microcytic hypochromic anemia suspect systemic lupus erythematosus, however in the patient in this case report it could not be established as systemic lupus erythematosus, because the patient was not willing to be referred to Zainal Abidin General Hospital, Banda Aceh for treatment. further examination.